Direct enantioselective amination of α-ketoester catalyzed by tertiary amine thiourea: a new approach to chiral α-hydroxy-β-amino acid. Issue 28 (8th July 2015) - Fu, Ji-Ya; Wang, Qi-Lin; Gui, Yong-Yuan; Wang, Li-Xin
Graphical abstract: A highly enantioselective amination of α-ketoesters catalyzed by chiral tertiary amine thioureas was reported to afford α-hydroxy-β-amino acids with two continuous stereocenters in high yields and enantioselectivities. Abstract: A highly enantioselective amination of α-ketoesters catalyzed by chiral tertiary amine thioureas was reported to afford α-hydroxy-β-amino acids with two continuous stereocenters in high yields (up to 90%) and enantioselectivities (up to 93% ee).